Perlindungan Pekerja Anak sebagai Anak Buah Kapal (Studi Anak Buah Kapal Nelayan Juragan di Teluk Kabung Tengah Bungus) - Aisa, Nora; Lubis, Khairani; Fendri, Azmi (Universitas Ekasakti, 2023)
Child labor is a child who does any type of work that has a nature or intensity that can interfere with education, endanger safety, health and growth and development can be classified as child labor. The prohibition to employ children is contained in Article 68 of Law Number 13 of 2003 concerning Manpower which regulates the prohibition of employers employing children. However, the fact is that there are many child laborers, one of which is child labor as crew members in Teluk Kabung Tengah Bungus. The prohibition of working for children is intended to provide protection for children, child protection is all activities to ensure and protect children and their rights so that they can live, grow, develop, and participate optimally in accordance with the dignity of humanity, and receive protection from violence and discrimination. The problems in this study are (1); How is the protection of child laborers as crew members in Teluk Kabung Tengah Bungus (2); What are the factors that cause the existence of underage crew members employed in Teluk Kabung Tengah Bungus. This research is a type of empirical normative research that uses secondary data (literature) and is supported by primary data based on field research, such as observations, interviews, and surveys. Based on the results of the research, it can be described that the legal protection system for child laborers as crew members has not been implemented in accordance with the law.